EVALUATION OF THE DETERMINANTS OF SHADOW ECONOMY IN SELECTED CENTRAL ASIAN COUNTRIES - Shokhjahon, Elmurodov; Akmal, Allakuliev; Buvsara, Tashmuradov; Samariddin, Elmirzaev; Shavkat, Hamdamov (International Journal of Psychosocial Rehabilitation, 2020)
This paper focuses on the evaluation of the determinants of shadow economy in Kazakhstan, Kyrgyz Republic and Tajikistan over 2005 to 2015. Our empirical research shows that more than 80 percent of the scope of the shadow economy in these countries can be explained by determinants such as total labor force, tax rate as a percent of commercial profit, labour participation rate, GDP per capita and imported goods and services as a percent of GDP. High rate of taxes and total labour force have positive impact on the scope of shadow economy, because firms evade the taxes pay salaries in “envelopes”.